Pemodelan Rantai Suplai Berbasis Economic Production Quantity dengan Menerapkan Kredit Perdagangan Dua Eselon - Jaka Permana (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2019)
Implementation of the supply chain is felt more important and very useful in today’s era  of industrialization. But in the process of supply chain encountered  various  risks that may affect the flow of the supply chain so it can not run smoothly, such as interference or imperfectness  in transportations. This research  was made to propose a mathematical model for a supply chain under the effect of unexpected disruptions  in transport. Supplier/manufacturer offers the retailer  a trade credit period t1 , then the retailer offers the customer a credit with a period of t2  and finally the retailer receives the revenue from t2  ke T + t2 , where T is the cycle time at the retailer.  Under this situation,  the three cases such as T ≤ t1 ≤ T + t2 , T ≤ T + t1 ≤ t2, and  t1  ≤ t2 are discussed. An EPQ (Economic Production Quantity) based model is established and retailer’s optimal replenishment policy is obtained through mathematical theorems. From the results of testing on several cases, the best solution for the two procedures has been obtained, namely between risk neutral and risk averse solutions based on the level or number of items damaged/defective. If the number of items damaged is 2 units, then solution risk neutral is far better than the risk averse solution, whereas if the number of items is damaged 3 units, then the risk averse solution is far better than the risk neutral solution.